2007
DOI: 10.1002/jcc.20602
|View full text |Cite
|
Sign up to set email alerts
|

The way of stabilizing non‐IPR fullerenes and structural elucidation of C54Cl8

Abstract: Recently, a new non-IPR chlorofullerene C(54)Cl(8) was isolated experimentally (Science 2004, 304, 699). To explore the ways to stabilize non-IPR fullerenes, the authors studied all of the possible isomers of C(54) fullerene and some of the C(54)Cl(8) isomers at PM3, B3LYP/3-21G, and B3LYP/6-31G* levels. Combined with analysis of pentagon distributions, bond resonance energies, and steric strains, C(54):540 with the least number of 5/5 bonds was determined to be the thermodynamically best isomer for the C(54)C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 46 publications
1
30
0
Order By: Relevance
“…To fully stabilize C 56 via exohedral addition, the reaction needs to saturate all of the kinetically unstable 5/5 bonds sufficiently. [18,20,22] Hence, to identify the most stable C 56 Cl 10 , we consider the isomers with PA = 4 and PA = 5.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…To fully stabilize C 56 via exohedral addition, the reaction needs to saturate all of the kinetically unstable 5/5 bonds sufficiently. [18,20,22] Hence, to identify the most stable C 56 Cl 10 , we consider the isomers with PA = 4 and PA = 5.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Several theoretical studies have demonstrated that all of the kinetically unstable 5/5 bonds (CÀC bonds shared by two pentagons) of the cage should be saturated to stabilize the unconventional fullerene via exohedral additions. [18,20,22] As we know, in addition to the synthesis of C 50 Cl 10 , C 56 Cl 10 was also captured in chlorine-involving arc-discharge process. It is therefore necessary and interesting to find out which C 56 fullerene isomer is the best candidate for the parent fullerene for C 56 Cl 10 .…”
Section: Introductionmentioning
confidence: 98%
“…Besides, experimental investigations have also suggested that C 20 H 20 [18], C 50 Cl 10 [19], and C 56 Cl 10 [20] were energetically stable. For non-IPR fullerene derivatives, both theoretical and experimental investigations reported previously revealed that it was necessary to saturate all the active sites (the carbons atoms shared by two or three pentagons) [19,21,22]. Take C 50 Cl 10 as an example, 13 C NMR experimental and theoretical computation results demonstrated that the 10 chlorines were added to the total five fused pentagon pairs.…”
Section: Introductionmentioning
confidence: 95%
“…This suggests that non-IPR fullerenes might be stabilized by strain-relief through exohedral derivatization the fused pentagons [6][7][8][9][10][11][12]. For example, a series of non-IPR chlorofullerenes have been isolated by Xie et al [12] using the modified graphite arc-discharge process.…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, many computational studies have recently been conducted to predict possible structures and electronic properties of non-IPR fullerene exoderivatives, especially for those between C 60 and C 70 or smaller fullerenes that inevitably violate the IPR according to Euler's rule [13][14][15][16]. Among the many well-known exohedral reactions developed on the nanostructures, cycloaddition reactions constitute one of the most important and versatile procedures for functionalization of fullerenes [17,18].…”
Section: Introductionmentioning
confidence: 99%